Rancang Bangun Jig Welding Modifikasi Pneumatic Clamp Untuk Pengelasan Rear Tube Sepeda Motor Listrik - Sanurya Putri Purbaningrum; Edwin Sahrial Solih; Indah Kurnia Mahasih Lianny; Sarip Awaludin; Dirham Sidiq (P3M Politeknik Negeri Cilacap, 2025)
Welding of electric motorcycle rear tube frames at PT Ganding Toolsindo still uses manual clamp welding jigs, which cause problems with long part setup times and less precise weld joints. This study aims to design a more efficient welding jig, which can increase productivity and welding quality by modifying the pneumatic clamp on the welding jig used. The research methods used include literature studies, field observations, data analysis and collection, welding jig design with pneumatic clamps, manufacturing, and testing of welding jigs. Welding with manual clamp welding jigs requires a part setup time of 40 seconds. While the part setup in welding with pneumatic clamp modified welding jigs is 19 seconds. The reduction in part setup time by using pneumatic clamp modified welding jigs is 21 seconds or 52%. These results prove that the use of pneumatic clamp modified welding jigs can increase welding efficiency and produce more precise weld joints.